Peran Ustadz Dalam Membentuk Sikap Nasionalisme Santri di Pondok Pesantren Al-Fathimiyah Karawang - maruf, Muhammad Amar Ma’ruf; Muthoharoh; Agung (Jurnal Pendidikan Islam, 2025)
Abstract   This study was motivated by the importance of internalizing national values in Islamic boarding schools as Islamic educational institutions that play a strategic role in building national character. Islamic boarding schools function not only as places of spiritual guidance, but also as forums for shaping nationalism among the younger generation. This study aims to describe the role of ustadz in shaping the nationalism of students at the Al-Fathimiyah Islamic Boarding School in Karawang. The method used is descriptive qualitative, with data collection techniques through observation, in-depth interviews, and documentation. Data analysis is carried out interactively through the stages of data reduction, data presentation, and conclusion drawing. The results show that ustadz have a significant role in shaping the nationalistic attitudes of santri through their functions as educators, mentors, role models, and motivators. National values are integrated into religious learning activities and the daily activities of students through role modeling, habit formation, and national activities such as flag ceremonies, discussions on the value of unity, and social activities. In addition, teachers also face challenges such as limited resources, differences in student motivation, and the influence of outside cultures. These challenges are overcome through innovative learning methods, collaboration with pesantren administrators, and the balanced strengthening of religious and nationalist values. Thus, the active role of ustadz at the Al-Fathimiyah Karawang Islamic Boarding School contributes significantly to shaping students who have noble character, a nationalist spirit, and a balance between faith and love for the nation. Keywords: Role of Ustadz, Nationalism, Students, Islamic Boarding School, Character Building